L Learning Motivation Development of Elementary Students’s in Sukarame Village-Garut at COVID-19 Pandemic - Aika Latifah Alawiyah; Cindy Reporma; Mia Nurohmah; Muhammad Riki; Siti Julia Pastira (Indonesian Journal of Community Empowerment (IJCE), 2020)
At the end of 2019 to the beginning of 2020 the world experienced an extraordinary event, especially in the health sector, in the form of a viral pandemic that attacked globally. This virus is thought to have first appeared in China, precisely in the city of Wuhan, and is thought to have originated from fish and animal markets in the area. At the beginning of its appearance, WHO temporarily named it as 2019 novel coronavirus (2019-nCoV), then WHO announced a new name, namely Coronavirus Disease (COVID-19) which is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV2) virus. This is the basis of the problem in encouraging community service activities so that they can actively participate in efforts to prevent COVID-19. The purpose of this online learning spirit development activity is to prevent the spread of Covid-19 which is increasingly happening in Indonesia, so that students can learn well. The method used during this activity is in the form of directly assisting the student learning process by complying with health protocols and assisting online learning. As a result of the learning assistance activities, there has been a significant change from the habits of the surrounding community where stundest are more enthusiastic about learning and no confusion in doing assignments online.